Effect evaluation of kangaroo mother care in Liping area, Guizhou province,China - Wu Li; Zhao Yu; Yang Jing (BMC, 2022)
Abstract Backgroud Kangaroo mother care (KMC) refers to the mother and baby after the birth of the early start of continuous skin contact way of a newborn care, which is a simple operation, easy controlled and with low cost, no large or high consumption of equipment.So it is very suitable for developing in areas where medical resources are relatively scarce, such as GuiZhou province where is a relatively poor province in China with many ethnic minorities. Methods This study selected the pregnant women who gave birth in Liping County, Guizhou Province, China, as the research object, to explore the impact of kangaroo mother care on the physiologic status of newborns in liping county, Guizhou Province. Results A total of 347 hospitalized parturient women were divided into the KMC group and the control group. The results showed that the KMC group showed obvious advantages in stabilizing newborn vital signs, health indicators, promoting the success rate of breastfeeding and reducing newborn pain. Conclusions Research shows that kangaroo mother care is beneficial to postpartum maternal and infant health, and has advantages suitable for local characteristics, which is worth further promotion in minority areas of Guizhou Province.